Temperament and achievement motivation among athletes in team and individual disciplines - Matwiejczuka, P.; Lewickab, P. A.; Mazur, Z. (Acta Kinesiologica, 2025)
Purpose: This study aimed to examine differences in temperament and achievement motivation, as well as to determine the relationship between these variables among athletes in team and individual sports.